Flickers of Film : Nostalgia in the Time of Digital Cinema. - Sperb, Jason (Rutgers University Press, 2015)
Whether paying tribute to silent films in Hugo or celebrating arcade games in Wreck-It-Ralph, Hollywood suddenly seems to be experiencing a wave of intense nostalgia for outmoded technologies. Flickers of Film offers a nuanced look at the benefits and risks of this nostalgia, considering how it registers industry-wide uncertainty with the dominance of the digital, even as it ignores the people whose livelihoods have been most affected by the economic transformations of the digital era.